2019
DOI: 10.1093/nutrit/nuz031
|View full text |Cite|
|
Sign up to set email alerts
|

Role of fruit juice in achieving the 5-a-day recommendation for fruit and vegetable intake

Abstract: Although there is strong evidence that consumption of fruit and vegetables is associated with a reduced rate of all-cause mortality, only a minority of the population consumes 5 servings a day, and campaigns to increase intake have had limited success. This review examines whether encouraging the consumption of fruit juice might offer a step toward the 5-a-day target. Reasons given for not consuming whole fruit involve practicalities, inconvenience, and the effort required. Psychologically, what is important i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 106 publications
1
40
0
Order By: Relevance
“…This recommendation is also supported by a number of prominent experts, boards, and associations, such as the National Health Service (NHS) in Great Britain [97], American Heart Association (AHA) [98], Centers for Disease Control and Prevention (CDC) [99], and Office of Disease Prevention and Health Promotion (ODPHP) in the United States of America [100]. Moreover, not only the role of raw fruits and vegetables but also that of the processed fruits and vegetables, including frozen, canned, or cooked ones [101], as well as juices [102], is emphasized to meet the recommended intake.…”
Section: Discussionmentioning
confidence: 99%
“…This recommendation is also supported by a number of prominent experts, boards, and associations, such as the National Health Service (NHS) in Great Britain [97], American Heart Association (AHA) [98], Centers for Disease Control and Prevention (CDC) [99], and Office of Disease Prevention and Health Promotion (ODPHP) in the United States of America [100]. Moreover, not only the role of raw fruits and vegetables but also that of the processed fruits and vegetables, including frozen, canned, or cooked ones [101], as well as juices [102], is emphasized to meet the recommended intake.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that it has been demonstrated that the consumption of 800 g/day of fruit and vegetables reduces the risk of cardiovascular disease and mortality from all causes, and 600 g/day reduces the risk of cancer, the WHO and several dietary guidelines still recommend 400 g/day [5]. However, most of the population does not even reach the minimum established by health authorities, which is equivalent to five portions of fruits and vegetables a day [6,7]. The benefits related to a healthy lifestyle are known worldwide, with new products emerging that offer the possibility of incorporating the 2 of 14 aforementioned bioactive compounds through supplements/nutraceuticals, which helps to reach the nutritional recommendations [8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they ignore the nutritional value labeled on the food items. When they choose a meal in a restaurant, they prefer to eat delicious and diverse food, and snacks with high fat and calorie values [9,12].…”
Section: Discussionmentioning
confidence: 99%
“…High coffee consumption is associated with stroke, coronary heart disease, heart failure, liver cirrhosis, urinary tract infection, stomach upset, and more [8]. On the other hand, fruit juices are a rich source of vitamin C, carotenoids, and polyphenols, with health-promoting benefits [9].…”
Section: Introductionmentioning
confidence: 99%